iTKNE : building an online environment for transnational knowledge exchange in teacher education : final report 2014. - Tamatea, Laurence (Australia. Office for Learning and Teaching, 2014)
This report details the results of the iTKNe project, which commenced as an initiative to facilitate enhanced interaction between domestic teacher education students and international teacher education students in Australian universities. The principal outcome and deliverable of the project has been the creation of Educationlinx.com, which comprises an online learning management system built upon the Drupal framework. Educationlinx.com was envisaged as a resource that would respond to the needs for improvement in domestic students' engagement with international knowledge and Australian higher education's engagement with international students, as identified in the Bradley Review of Higher Education (2008). This concept received the support of eight Australian universities and drew inspiration from the innovative work undertaken by Professor Michael Singh at the University of Western Sydney, where the Research Orientated School-Engaged Teacher Education program (ROSETE) was successfully demonstrating new approaches to engagement with international students in teacher education. The report discusses how the project developed this ICT solution to enable knowledge exchange links across universities and the world at large. [Executive summary, ed]